From injectable to 3D printed hydrogels in maxillofacial tissue engineering: A review - Divya Mehrotra; Ruby Dwivedi; Deepti Nandana; R.K. Singh (Elsevier, 2020)
Introduction: This review aims at describing different types of hydrogels in context to their composition, fabrication techniques and other specific features along with an insight into the latest advancements including smart hydrogels, 3D printed, programmable, shape memory and self-healing hydrogels for their applicability as scaffold in maxillofacial bone and cartilage tissue regeneration. Methods: Electronic database searches were undertaken on PubMed, Ovid, Medline, Embase, ProQuest and science direct for English language literature, published for application of hydrogels in maxillofacial bone and cartilage tissue engineering. The search items used in this article were hydrogel, bone and cartilage tissue engineering, maxillofacial, clinical trials. Reviews and in vitro studies were excluded. Results: Search for injectable hydrogel showed 4955 articles, when restricted to bone tissue engineering results were reduced to 463 and for cartilage engineering to 335; when we limited it to maxillofacial bone and cartilage tissue engineering, search results showed 49 articles to which 9 additional articles were included from references, after exclusion of in-vitro studies and duplicates 16 articles were obtained for our study. Similarly, for 3D printed hydrogels, result showed 1126 articles, which got restricted to 19 when searched for maxillofacial bone and cartilage engineering, then 2 additional articles were included directly from references, and finally after exclusion of the invitro studies and duplicates, a total of 5 articles were obtained. Conclusion: Modifications in hydrogel can improve the mechanical properties, biocompatibility and unique chemistries for its use in bone and cartilage tissue engineering for future research